Psychometric assessment of the Post- Secondary Student Stressors Index (PSSI) - Brooke Linden; Heather Stuart (BMC, 2019)
Abstract Background Previous research has linked excessive stress among post-secondary students to poor academic performance and poor mental health. Despite attempts to ameliorate mental health challenges at post-secondary institutions, there exists a gap in the evaluation of the specific sources of stress for students within the post-secondary setting. Methods The goal of this study was to develop a new instrument to better assess the sources of post-secondary student stress. Over the course of two years, the Post-Secondary Student Stressors Index (PSSI) was created in collaboration with post-secondary students as co-developers and subject matter experts. In this study, we used a combination of individual cognitive interviews (n = 11), an online consensus survey modeled after a traditional Delphi method (n = 65), and an online pre- (n = 535) and post-test (n = 350) survey to psychometrically evaluate the PSSI using samples of students from Ontario, Canada. We collected four types of evidence for validity, including: content evidence, response processes evidence, internal structure evidence, and relations to other variables. The test-retest reliability of the instrument was also evaluated. Results The PSSI demonstrated strong psychometric properties. Content validation and response processes evidence was derived from active student involvement throughout the development and refinement of the tool. Exploratory factor analysis suggested that the structure of the PSSI reflects the internal structure of an index, rather than a scale, as expected. Test-retest reliability of the instrument was comparable to existing, established instruments. Finally, the PSSI demonstrated good relationships with like measures of stress, distress, and resilience, in the hypothesized directions. Conclusions The PSSI is a 46-item inventory that will allow post-secondary institutions to pinpoint the most severe and frequently occurring stressors on their campus. This knowledge will facilitate appropriate targeting of priority areas, and help institutions to better align their mental health promotion and mental illness prevention programming with the needs of their campus.